Standardization of chemicals for improving post harvest life of loose flowers of tuberose (Polianthes tuberosa) - CHAWLA, S L; BHATT, DIPAL; PATIL, SUDHA; CHAUDHARI, PARMESHVARI (The Indian Journal of Agricultural Sciences, 2020)
An experiment was carried out to study the effect of various concentrations of boric acid and sodium benzoate on post harvest life of loose flowers of tuberose for three years from 2016 to 2018 under AICRP on Floriculture. The experiment was laid out in completely randomized design with four replications consisting eight treatments of chemicals, viz. boric acid (2, 3, 4 and 5%), sodium benzoate (10, 25 and 50 ppm) and control. The results of pooled analysis of three years indicated that the florets (loose flowers) of tuberose treated with 4% boric acid significantly improved the post harvest life with the minimum change in fresh weight of florets (6.91, 17.38, 29.67 and 45.74% ), maximum fresh flower (98.67, 81.00, 56.00 and 35.00%) at 12, 24, 36 and 48 hours, respectively. Application of 4% boric acid also recorded significantly maximum number of opened flowers (5.17), half opened flowers (4.67) as well as minimum closed flowers (15.17) at 48 hr out of 25 flowers. The maximum longevity (39.33 hr), minimum rotting at 48 hr (40.25%) and highest score of acceptability at 36 hr as per hedonic scale (8.05) were also recorded in the same treatment. Quick dip of loose flowers of tuberose in 4% boric acid was found beneficial for improving post harvest life of loose flowers with 56% fresh up to 36 hr.